2020
DOI: 10.1186/s12913-020-05171-z
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of clinical practice guideline on antimicrobial in China: an exploratory survey on multilevel determinants

Abstract: Background: Nowadays, irrational use of antimicrobials has threatened public health. It's necessary to expand the use of clinical practice guideline (CPG) on antimicrobial for facilitating the proper use of antimicrobial. However, the utilization status of CPG on antimicrobial and the influencing factors, especially the ones at the organizational level, remain largely unknown. Methods: A cross-sectional questionnaire survey was conducted on a sample among physicians from 16 public hospitals in the eastern, cen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Supportive leadership and management that facilitate guideline implementation are also cited as major enablers of guideline adoption 3 14 16–18 20–22 24 25 27 30 32 33 38 40 43 44 46 49 52 53. Leadership and management that encourage guideline use require dissemination of the explicit details of the implementation strategy for guideline use 40 48 52…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supportive leadership and management that facilitate guideline implementation are also cited as major enablers of guideline adoption 3 14 16–18 20–22 24 25 27 30 32 33 38 40 43 44 46 49 52 53. Leadership and management that encourage guideline use require dissemination of the explicit details of the implementation strategy for guideline use 40 48 52…”
Section: Resultsmentioning
confidence: 99%
“…The use of clinical guidelines can be constrained by healthcare provider perceptions of the guidelines, including their confidence in the quality of clinical guidelines,37 42 44 views on whether the use of clinical guidelines threatens their professional autonomy,21 25 32 54 interest in or attitude to evidence-based management,13 16 22 prioritising experience or personal beliefs 14 19 27 43 47. Individual beliefs on the consequences of guideline adherence including clinical outcomes, improving drug prescription efficiency, time and money savings and legal repercussions were also enablers in clinical guideline usage 30 35 52…”
Section: Resultsmentioning
confidence: 99%
“…In terms of hospital level, it is reported that physicians’ intentions and utilization of using CPGs on antimicrobials were significantly influenced by top management support [ 48 ]. As influential people in the hospitals, top managers play important roles in developing the organizational vision and culture, as well as shaping the expected behavior and norms of physicians [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the TPB has been applied in considerable research about health professionals' intentions, 10 including the acceptance of innovative health technology, 11,12 and the adherence to clinical guidelines. 13 Moreover, numerous TPB studies have explained over fifty percent of the total variance of intentions. [14][15][16] According to Ajzen, "TPB is principally open to the inclusion of additional predictors if it can be shown that they capture a significant proportion of the variance".…”
Section: Introductionmentioning
confidence: 99%